Teaching behaviour change skills to undergraduate medical students - Grey, Ian (2013)
This study investigates the effects of a three-week student project where students selected a healthbehaviour and implemented a self-management program to increase or decrease that behavior. Behaviours were (1) smoking reduction, (2) caffeine reduction, (3) reduction in consumption of saturated fats, (4) increasing physical activity and (5) increasing consumption of fruit and vegetables. 121 first year medical students conducted a seven day baseline assessment of the selected behavior. Students implemented a behavior change program over fourteen consecutive days based upon 2 hours of lecture material covering principles of operant learning, the Health Belief Model and the Theory of Planned Behavior. Students also completed pre and post questionnaires on identifying barriers to change and experiences of the project. Results indicated substantial changes in targeted behaviours. The most frequently used interventions were positive reinforcement (64%), goal setting (63%) and activity scheduling (47%). Students indicated positive attitudes to the project. Providing students with experience of application of behavior change principles on themselves offers one route to the establishing behaviour change as a clinical competency. However, disparities and lack of focus in existing social and behavioural science curricula may mitigate against the prioritization of this skill being established.